A new species in the genus Alectorolophus Brunner von Wattenwyl, 1898 from Indonesia with discussion on its position compared to allied genera in subfamily Catantopinae (Orthoptera: Acrididae) - Storozhenko, Sergey Yu.; Kim, Taewoo (Zootaxa, 2016)
Alectorolophus impunctus Storozhenko et Kim, sp. nov. from Sulawesi Island, Indonesia, is described here. Keys to both sexes of all known species and subspecies of Alectorolophus are also provided in this report. The position of genus Alectorolophus in the systematics of grasshoppers is clarified. It belongs to subtribe Ecphantina (Catantopinae: Catantopini) consisting of nine genera distributed in Australia and Oriental regions. The diagnosis of Ecphantina is clarified and a key to genera is provided. An annotated list of the genera and species of Ecphantina is given. Moreover, the correct name of the subfamily Coptacridinae is Coptacrinae Brunner von Wattenwyl, 1893.